Analisis Faktor Keterlambatan Proyek Gedung Pabrik Buduran Sidoarjo dan Rekomendasi Penyelesainnya - Kota, Aprintius Tuanah; Dzinnur, Cilda Thesisa Ilmawan; Qordhowi, Andrian Firdaus Yusuf Al (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The purpose of this study is to determine the optimal time for implementation and identify factors that cause delays in the construction project at the Buduran Factory Building in Sidoarjo. In this construction project, obstacles occurred that could result in material and moral losses. This study is a qualitative study using the Critical Path Method. The results of this study indicate that in the calculation of the critical path method for the Buduran Factory Building project in Sidoarjo, there are factors that can cause project delays, namely weather, materials, and a reduction in workers.